A vocabulary for sustainability. Issue 1 (31st December 2022) - Bova, Demetrio Miloslavo
ABSTRACT: The definitions of sustainability and sustainable development in the literature often appear contrasting and contradictory, raising the need for clarification and standardization. This manuscript introduces a formal vocabulary for sustainability to achieve word and meaning standardization for sustainability researchers and strategists. It formalizes key concepts such as processes, systems, ecosystem, sustainability, development and adaptation by providing an English description and a mathematical formalization. These support a high degree of consistency and applicability for science and explicit the approximations needed to deal with the complexity of the specific context they inquire about. The clarifications also allow the author to conclude distinguishing sustainability, its necessary conditions and related strategies. He shows that sustainability may need exploitation, adaptation, parasitism, or mutualism, which these must not be confused with sustainability itself, and that mutualism entails the most extended longevity.